Bibliography: Latin American Scientific and Technical Information Issues - Vilma Lopez Correia (Issues in Science and Technology Librarianship, 1993)
This bibliography was extracted from an independent study project by Vilma Lopez Correia at the College of Library and Information Sciences, University of Maryland, July 1993. It was handed out at the SLA State of the Art Institute.